Direct hemoperfusion using a polymyxin B‐immobilized polystyrene column for COVID‐19. Issue 3 (15th December 2020) - Katagiri, Daisuke; Ishikane, Masahiro; Asai, Yusuke; Izumi, Shinyu; Takasaki, Jin; Katsuoka, Hiyori; Kondo, Isao; Ide, Satoshi; Nakamura, Keiji; Nakamoto, Takato; Nomoto, Hidetoshi; Akiyama, Yutaro; et al.
Abstract: Objective: To evaluate the efficacy and safety of direct hemoperfusion using a polymyxin B‐immobilized polystyrene column (PMX‐DHP) in severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)‐positive pneumonia patients. Methods: This study was a case series conducted at a designated infectious diseases hospital. Twelve SARS‐CoV‐2‐positive patients with partial pressure of arterial oxygen/percentage of inspired oxygen (P/F) ratio < 300 were treated with PMX‐DHP on two consecutive days each during hospitalization. We defined day 1 as the first day when PMX‐DHP was performed. PMX‐DHP efficacy was assessed on days 7 and 14 after the first treatment based on eight categories. Subsequently, improvement in P/F ratio and urinary biomarkers on days 4 and 8, malfunctions, and ventilator and extracorporeal membrane oxygenation avoidance rates were also evaluated. Results: On day 14 after the first treatment, disease severity decreased in 58.3% of the patients. P/F ratio increased while urine β2‐microglobulin decreased on days 4 and 8. Cytokine measurement pre‐ and post‐PMX‐DHP revealed decreased levels of interleukin‐6 and the factors involved in vascular endothelial injury, including vascular endothelial growth factor. Twenty‐two PMX‐DHPs were performed, of which seven and five PMX‐DHPs led to increased inlet pressure and membrane coagulation, respectively. When the membranes coagulated, the circuitry needed to be reconfigured. Circuit problems were usually observed when D‐dimer and fibrin degradation product levels were high before PMX‐DHP. Conclusions: Future studies are expected to determine the therapeutic effect of PMX‐DHP on COVID‐19. Because of the relatively high risk of circuit coagulation, coagulation capacity should be assessed beforehand.